2009
DOI: 10.1126/science.1178336
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Wealth Transmission and the Dynamics of Inequality in Small-Scale Societies

Abstract: Small-scale human societies range from foraging bands with a strong egalitarian ethos to more economically stratified agrarian and pastoral societies. We explain this variation in inequality using a dynamic model in which a population’s long-run steady-state level of inequality depends on the extent to which its most important forms of wealth are transmitted within families across generations. We estimate the degree of intergenerational transmission of three different types of wealth (material, embodied, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
287
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(328 citation statements)
references
References 34 publications
11
287
0
5
Order By: Relevance
“…To take an empirical approach to this question in humans, we collated the data of human behavioral ecologists who have collected largely comparable demographic data in primarily predemographic transition, small-scale communities across the world [28,29]. Using both published sources and personal communications on these 15 populations, we examine the The Kipsigis of Kenya also practice polygyny, but men engage in scramble competition to secure the resources that attract newly initiated young women; men with more resources acquired through trade, theft, and inheritance are those with multiple wives [59].…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation
“…To take an empirical approach to this question in humans, we collated the data of human behavioral ecologists who have collected largely comparable demographic data in primarily predemographic transition, small-scale communities across the world [28,29]. Using both published sources and personal communications on these 15 populations, we examine the The Kipsigis of Kenya also practice polygyny, but men engage in scramble competition to secure the resources that attract newly initiated young women; men with more resources acquired through trade, theft, and inheritance are those with multiple wives [59].…”
Section: Glossarymentioning
confidence: 99%
“…Our data do not support this possibility; some high I s populations are polygynous (e.g., Kipsigis, where some men have up to 12 wives), whereas others exhibit almost exclusively monogamous marriage (e.g., the Hadza). In fact, there is no apparent patterning of the societies in terms of type or stability of marriage, or indeed of the economy (farming, foraging, or herding), although more systematic comparative analysis with bigger samples using individual level data is warranted [28,29]. Furthermore, it is worth noting that, in nonhumans, higher rates of polygyny do not necessarily mean greater sexual selection on males [32,33].…”
Section: Box 1 Changing the Direction Of The Causal Arrow Between Pimentioning
confidence: 99%
“…The extent to which resources are transferred across generations will influence competition between siblings in adulthood, when resource transfers determine chances of marriage and future means of production [33,40]. This may explain why trade-off effects have proved easier to demonstrate in agriculturalist populations rather than hunter -gatherers, where resource inequality and intergenerational resource transmission are both relatively low [8]. Supporting this explanation, Voland & Dunbar [36] found that negative effects of large family size were unique to landowning families in the Krummhö rn, while for peasants, offspring success was determined by other means.…”
Section: (B) Socioecological Contextmentioning
confidence: 99%
“…Demographers and anthropologists have long recognized that all human societies limit birth rates to some extent, ensuring that few women reach the biological maximum, even under the most favourable conditions [5,6]. Human offspring are also born highly vulnerable and slowmaturing, remaining an energetic burden on parents and extended kin often well into the second decade [7], and in many societies later transfers of wealth at marriage and inheritance are substantial [8,9]. Thus, there is good reason to believe that a trade-off between quantity and 'quality' of offspring is fundamental to human life history.…”
Section: Introductionmentioning
confidence: 99%
“…As some of these wealth inheritance patterns have been interpreted as signatures of vertical transmission of socially learned information [71,74], cultural traits associated with child mortality risk may be influenced by cultural inheritance patterns. Typically, such cultural inheritance patterns would be interpreted as simply one mechanism through which our species adapts its behaviour to the local ecology, but this human behavioural ecology perspective also does not necessarily preclude the notion that such cultural inheritance patterns could potentially operate independently of the influences of ecological variables.…”
Section: Integrating Evolutionary Perspectives On Human Behaviourmentioning
confidence: 99%